CONSTRUCTION OF COMPUTATIONAL THINKING IN THE EARLY YEARS OF ELEMENTARY SCHOOL: A CARTOGRAPHIC ANALYSIS - Pescador, Cristina M.; Schmidt, Sintian; Bona, Aline Silva De (Revista Ciranda, 2020)
This study intends to map and identify signs of the construction of computational thinking by second-grade students from an elementary municipal school in Rio Grande do Sul. During some periods, during regular classes developed at the school’s computer lab, the children were challenged to solve problems sometimes using a programmable robot, or developing activities proposed by the website “Hour of code”, or working with programming activities on a software called Scratch. The research method is based on principles of Cartography as proposed by Kastrup, based on Deleuze and Guattari. The analysis of how students tried to solve the problems presented is carried out considering concepts of computational thinking (WING), coding literacy (DUDENEY et al) and digital abilities (PAPERT). The results point out children’s autonomous learning process and evidences of abstraction in solving the activities proposed. They also show children’s collective actions/thoughts while sharing solutions with their peers, their way.